PENGARUH EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Jannah, Ayu Roudhatul; Efendi, Bakhtiar (JURNAL ILMIAH EDUNOMIKA, 2024)
Export is the simplest form of international trade and is a strategy in marketing production abroad. This study aims to determine the effect of exports on economic growth with a mediating variable, namely the exchange rate. This research method is a research method with a quantitative approach supported by secondary data sourced from the Central Bureau of Statistics and the World Bank (World Bank) with a research time of 2009 to 2023. The research data analysis technique used is path analysis. The results explain that exports influence economic growth. Exports as a driving force for GDP, where exports can expand markets, can encourage the flow of capital, and will generate foreign exchange. When exports increase, economic growth also increases and vice versa if exports decrease, economic growth decreases. And the exchange rate can be a mediating variable of the indirect effect of the export variable on the economic growth variable. This means that exports can be a factor that can influence directly without the mediation of other variables. The higher the real exchange rate, the more it will encourage exports and others and be able to affect Indonesia's economic growth.